1997
DOI: 10.1177/00220345970760081301
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Cytotoxicity and Fluoride Release of Resin-modified Glass-ionomer Cements

Abstract: New-generation glass-ionomer cements contain resin to improve their restorative properties. These resin-modified glass-ionomer cements vary considerably in their chemistry, which could result in corresponding variability in their physical and biological properties. This study investigated the cytotoxicity and the fluoride release of two resin-modified glass ionomers, a conventional glass-ionomer cement, and a resin composite. Samples were prepared and extracted in distilled water for 1, 4, and 7 days; eluates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 20 publications
4
34
0
Order By: Relevance
“…Two rmGlCs (VitrebondiM and Vitremeri\'( reduced protein synthesis of human gingival fibroblasts by 00°o, whereas the four tested conventional GlCs caused significantly less inhibition of protein synthesis. Severe cytotoxicity of Vitremert'N in perma nent 3T3 fibroblasts was also found by Kan et al (1997).…”
Section: (Vi) Dentin Adhesives (A) Composition and Release Of Substancesmentioning
confidence: 86%
“…Two rmGlCs (VitrebondiM and Vitremeri\'( reduced protein synthesis of human gingival fibroblasts by 00°o, whereas the four tested conventional GlCs caused significantly less inhibition of protein synthesis. Severe cytotoxicity of Vitremert'N in perma nent 3T3 fibroblasts was also found by Kan et al (1997).…”
Section: (Vi) Dentin Adhesives (A) Composition and Release Of Substancesmentioning
confidence: 86%
“…24 Fluoride release and cytotoxicity were correlated, although the fluoride release did not account for the cytotoxicity observed. In their opinion, there were factors other than fluoride responsible for the cytotoxicity.…”
Section: Discussionmentioning
confidence: 97%
“…[29][30][31] Although the fluoride-release potential of GICs has often been cited as a reason to use this material and its derivatives for the restoration of primary teeth, it should be noted that the amount of fluoride released varies between brands. 32 In the present study, fissure sealant was applied after etching, to both the remaining pits and fissures and also to the set surface of the RMGIC. Sidhu and Sherriff, 33 and Ribeiro 34 showed that the susceptibility of GIC material to dehydration had not been significantly reduced by the addition of resin in RMGIC, and suggested that surface protection helps with water balance.…”
Section: Discussionmentioning
confidence: 99%